PENGELOLAAN SARANA DAN PRASARANA PENDIDIKAN SEBAGAI UPAYA PENINGKATAN KUALITAS PENDIDIKAN - Khuturoh, Rofaha Nur; Khoirunnisa, Salma Muthia; Ramadhan, Muhammad Fadhil; Munawwaroh, Zahrotul (STKIP Pesisir Selatan, 2026)
The quality of education is largely determined by the availability and management of adequate facilities and infrastructure. This study aims to analyze the management system for educational facilities and infrastructure and its impact on improving the quality of education in Islamic schools (madrasahs). The research method used a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews with madrasah principals and administrative staff, and documentation studies at junior high schools (madrasahs). Data were analyzed using descriptive analysis techniques to illustrate the management patterns implemented. The results indicate that effective management of facilities and infrastructure encompasses four main stages: needs planning based on analysis of real conditions, procurement according to quality standards and priorities, optimal utilization in the learning process, and routine maintenance to maintain functionality. Madrasahs with a structured and systematic management system show significant improvements in the quality of learning, reflected in increased student motivation, teacher teaching effectiveness, and academic achievement. The study's conclusion emphasizes that professional and sustainable management of facilities and infrastructure is a strategic investment for improving the overall quality of education.